Effects of nutrient deficits on growth, physio-biochemical changes, and yield of chilli (Capsicum annuum L.) grown in soilless culture - Abd. Razak, A'Fifah (2013)
Chilli (Capsicum annuum L.) is one of the most important vegetable crops commonly grown in soilless culture. It is widely consumed in Malaysia. Limited fresh water resources and fluctuating fertilizer prices, as well as excessive fertigation used by local growers, have led to higher costs and also wastage in water and fertilizer use. Deficit fertigation (DF) and fertigation frequency are irrigation strategies that imposed plants to nutrient deficit, which can improve fertigation use efficiency (FUE) without significant reduction in yield. Therefore, in the present study, the effects of different levels of DF and fertigation frequency on yield, growth, physiological and biochemical responses of chilli plants under soilless culture was evaluated and compared with the standard local grower’s practice (control). Plants subjected to control employing fertigation practice as recommended by the Department of Agriculture, Malaysia. Deficit fertigation (100, 75, 50 and 30% ETc) led to reduce in plant growth, dry matter partitioning into plant parts, total dry mass, photosynthetic rate, stomatal conductance, fresh fruit yield and FUE compared to control. In addition, different fertigation frequencies viz daily fertigation, one, two and three day fertigation intervals have shown significantly reduced plant growth, decreased photosynthetic rate, stomatal conductance, relative chlorophyll content and resulted in reduced fresh fruit yield. However, FUE was higher in fertigation frequency treatments than in the control. Deficit fertigation (100, 75 and 50% ETc) corresponding to two day fertigation intervals resulted in decreased substrate moisture content (SMC), plant growth, photosynthetic rate, stomatal conductance and relative chlorophyll content. The nutrient contents in the leaves as well as P, Ca and Mg were decreased in DF compared to control at the fruit ripening stage. Antioxidant enzymes such as catalase (CAT), ascorbate peroxidase (APX), guaiacol peroxidase (GPX) and proline significantly increased in DF compared to control, but decreased progressively by growth stages. Fresh fruit yield decreased in DF compared to the control, but FUE values in 100% ETc with two day fertigation intervals were higher than in the control but no significant difference with 100% ETc daily fertigation and 75% ETc with two day fertigation intervals. An attempt has been made to improve yield and increase FUE by increasing the levels of fertigation and use of dual-Kc. Result demonstrated that there were slight reduction in plant growth and total dry mass under 200% ETc and dual-Kc compared to control presumably attributed to the higher photosynthetic rate and stomatal conductance. Plants grown in 200% ETc and dual-Kc reduced 24% of fresh fruit yield and saved 29% of the amount of nutrient solution applied compared to control. However, plants supplied with 200% ETc dual-Kc employing six times fertigation scheduling has shown improved root growth, no significant difference in the total leaf area and dry matter partitioning to the plant parts with the control. The photosynthetic rate, stomatal conductance and leaf water potential on 15:00 h were enhanced in six fertigation scheduling compared to control. Six times fertigation scheduling improved FUE value and saved 35% of nutrient solution compared to control as well as no significant difference in ripe fresh fruit yield with the control. Therefore, this fertigation strategy could be the best water and nutrients saving strategy of chilli grown in soilless culture.